2020
DOI: 10.1073/pnas.1918279117
|View full text |Cite
|
Sign up to set email alerts
|

How social network sites and other online intermediaries increase exposure to news

Abstract: Research has prominently assumed that social media and web portals that aggregate news restrict the diversity of content that users are exposed to by tailoring news diets toward the users’ preferences. In our empirical test of this argument, we apply a random-effects within–between model to two large representative datasets of individual web browsing histories. This approach allows us to better encapsulate the effects of social media and other intermediaries on news exposure. We find strong evidence that inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
85
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(97 citation statements)
references
References 14 publications
10
85
0
2
Order By: Relevance
“…Most importantly, the patterns of ideological segregation that we identify here explain a small percentage of the variance in news diets, while coexposure grows denser and, therefore, less fragmented. This is consistent with previous research analyzing longitudinal data ( 4 , 13 ) and with studies on the mechanisms that shape online news diets, mostly aggregators and social media, which prior research has shown can actually boost coexposure to diverse content ( 12 , 21 , 22 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Most importantly, the patterns of ideological segregation that we identify here explain a small percentage of the variance in news diets, while coexposure grows denser and, therefore, less fragmented. This is consistent with previous research analyzing longitudinal data ( 4 , 13 ) and with studies on the mechanisms that shape online news diets, mostly aggregators and social media, which prior research has shown can actually boost coexposure to diverse content ( 12 , 21 , 22 ).…”
Section: Discussionsupporting
confidence: 91%
“…This results in a less partisan media environment than commonly accepted ( 11 ). Numerous studies depict news diets that are more varied than often assumed, at least for those who consume news ( 9 , 12 ). Some provide evidence that suggests a significant overlap between Democrats’ and Republicans’ news diets ( 13 ).…”
mentioning
confidence: 99%
“…Most importantly, the patterns of ideological segregation that we identify here explain a small percentage of the variance in news diets, while coexposure grows denser and, therefore, less fragmented. This is consistent with previous research analyzing longitudinal data (4, 13) and with studies on the mechanisms that shape online news diets, mostly aggregators and social media, which prior research has shown can actually boost coexposure to diverse content (12,21,22).…”
Section: Discussionsupporting
confidence: 92%
“…Combining different types of data provides also a far more refined insight on how political information and content impacts individuals differently (Popa et al, 2020;Scharkow et al, 2020;Wells & Thorson, 2017), possibly exacerbating already existing inequalities in political information of high quality. Designs employing digital trace and individual level data are, similarly, able to answer a number of new questions related to political communication during electoral campaigns.…”
Section: Asking Better Questions: the Potential Of Css In Political Cmentioning
confidence: 99%